Determinação de elementos traço em petróleos e em águas de produção por espectrometria de absorção atômica - Brandão, Helen Moura Pessoa (2012)
In this work, the development of procedures for the determination of trace elements in crude oil and produced water samples, using flame atomic absorption spectrometry (F AAS) and graphite furnace atomic absorption spectrometry (GF AAS) were presented. Ca, Mg and Sr were determined in crude oil and produced water samples by F AAS, while Ba and Cr were determined in crude oil samples byGF AAS. Ca, Mg, Sr and Ba were determined in crude oilsamples(13-38°API) after the analyte stabilization by emulsion formation, and for the determination of Cr in crude oil samples (8-38° API) three pre-treatment procedures were developed and compared: dilutionwith toluene, emulsionformation and direct sampling. The determination of Ca, Mg and Sr in produced waterwere realized using samples diluted with 0.2% v/v HNO3. The determinationswere carried out using analytical curves with aqueous standards as calibration method, and forCr determinationafter dilutionwith toluene it was used organometallic standard. The precision and accuracy of the developed procedures were verified by recovery tests, analysis of a standard reference material (NIST 1085b) and the comparison with other procedures. The recovery values were among96 and 104% for the developed procedures and results obtained for Ca, Mg, Ba and Cr in the certified reference material were concordant with reference values. All procedures showed good linearity (R2> 0.997) and the limits of detection (LOD) in the sample were: 0.54 µg g-1for Ca, 0.089 µg g-1for Mg, 0.10 µg g-1for Sr , 40 ng g-1for Ba, 0.73 ngg-1for Cr (direct sampling), 1.9 ng g-1forCr (thesample dilution with toluene) and 2.8 ng g-1for Cr (the emulsion formation). Thus, it was verified that the developed procedures are suitable for determination of Ca, Mg, Sr, Ba and Cr in crude oil samples. However, the results indicated that the Cr for toluene dilution is not recommended for samples with API grade of less than 15. The measurements in produced water samples were performed using analytical curves with aqueous standards as calibration method. The LOD obtained in the samples were 87.1 µg mL-1for Ca, 128 µg mL-1for Mg and 7.61 µg mL-1for Sr. The accuracy verification was performed by recovery tests and by comparison of the results with those obtained by ASTM methods, ASTM D 511-08 for Ca and Mg, and ASTM D 3352-08 for Sr. Good recovery values (94-111%) were obtained and the results between proposed procedures and ASTM methods agreed with each other (paired t-test, p<0.05). Thus, the determination of Ca, Mg and Sr in the produced water samples by F AAS after dilution with 0.2% v/v HNO3 showed an adequateprocedure.